Strategi Pembelajaran Diferensiasi Mengatasi Kesulitan Belajar Peserta Didik - Pangeran Iqbal; Dori Juli Andra; Gusmaneli Gusmaneli (Universitas Maritim AMNI Semarang, 2024)
Learning strategies are approaches or methods used to teach and help students understand subject matter more effectively. Learning is the main key in Education, of course the use of the right strategy will have a positive impact on the development of learning and understanding of students.success in Education is certainly the main concern of all of us, In this study will discuss the differentiation learning strategy where this differentiation learning strategy is a learning model where educators provide an approach that allows overcoming learning difficulties faced by students.